2009
DOI: 10.1371/journal.pone.0004258
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus (MRSA) Strain ST398 Is Present in Midwestern U.S. Swine and Swine Workers

Abstract: BackgroundRecent research has demonstrated that many swine and swine farmers in the Netherlands and Canada are colonized with MRSA. However, no studies to date have investigated carriage of MRSA among swine and swine farmers in the United States (U.S.).MethodsWe sampled the nares of 299 swine and 20 workers from two different production systems in Iowa and Illinois, comprising approximately 87,000 live animals. MRSA isolates were typed by pulsed field gel electrophoresis (PFGE) using SmaI and EagI restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
380
6
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(410 citation statements)
references
References 25 publications
19
380
6
5
Order By: Relevance
“…Although ST398 is identified commonly in pigs and farming environments in North America [73,[92][93][94][125][126][127][128][129][130][131][132][133], there appears to be a greater diversity of molecular types found on North American farms compared with those in Europe, where ST398 remains the dominant or sole strain of MRSA identified. One study in Michigan found no ST398 present in the pigs sampled [134], whereas the bulk of studies have found a mix of Bhuman^types (such as ST8 and ST5) in conjunction with ST398.…”
Section: Evolution Of La-mrsa In North Americamentioning
confidence: 99%
“…Although ST398 is identified commonly in pigs and farming environments in North America [73,[92][93][94][125][126][127][128][129][130][131][132][133], there appears to be a greater diversity of molecular types found on North American farms compared with those in Europe, where ST398 remains the dominant or sole strain of MRSA identified. One study in Michigan found no ST398 present in the pigs sampled [134], whereas the bulk of studies have found a mix of Bhuman^types (such as ST8 and ST5) in conjunction with ST398.…”
Section: Evolution Of La-mrsa In North Americamentioning
confidence: 99%
“…Methicillin resistant S. aureus is emerging as a zoonotic and veterinary bacterial pathogen of public health importance (Smith et al, 2009;Springer et al, 2009). It is a zoonosis that has garnered the attention of scientists and the public in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Plus de 50 % des souches sont de type SARM. Une enquête plus récente menée aux USA, en particulier dans l'Iowa et l'Illinois, principales régions américaines de production porcine, montre une prévalence de SARM de l'ordre de 49 % chez le porc, bien que variable avec l'âge, et de 45 % chez les porchers (Smith et al 2009). Le typage des souches par la technique MLST montre l'existence unique de ST398, en particulier chez ce type d'éleveur, alors que les types habituels observés chez les patients dans ce pays étaient USA100, USA300 et USA400.…”
Section: Quelques Caractéristiques Des Souches St398unclassified